MEDIA ABACUS TERHADAP KEMAMPUAN MENGENAL OPERASI HITUNG BILANGAN MATEMATIKA SISWA TUNANETRA DI SLB - taufik insani, moh (Jurnal Pendidikan Khusus, 2017)
ABSTRACT                 Blind students experience obstacles in learning to count. The result of preliminary observation at SLB Negeri Praya have 6 children with low learning ability of mathematics. These limitations make it difficult for students to digest any given learning, thus requiring learning media that can be used to improve the ability of students with visual impairment. One of them uses an abacus media. Therefore, the purpose of this study is to prove whether or not the influence of media abacus on the ability to recognize the operation of the mathematics of blind students in SLB Negeri Praya.                 Other research design using a quantitative approach to the type of the one group pre-test and post-test. The research subjects examined included 6 students in a state of blind students in total research was conducted using a 6x treatment with statistical calculations found that while Ztabel 1,96 2,05 Zh means Ho rejected and Ha received proved that Abacus Media Capabilities Against Influential Operation Count Math of Blind Student of Grade IV at SLB Negeri Praya "   Keywords: arithmetic operations, media abacus